Treasure Hunters - Patterson, James (Jimmy Patterson Books, 2013)
From #1 New York Times bestselling author James Patterson comes a brilliantly original adventure series, jam-packed with action, humor, and heart! The Kidd siblings have grown up diving down to shipwrecks and traveling the world, helping their famous parents recover everything from swords to gold doubloons from the bottom of the ocean. But after their parents disappear on the job, the kids are suddenly thrust into the biggest treasure hunt of their lives. They'll have to work together to defeat dangerous pirates and dodge the hot pursuit of an evil treasure hunting rival, all while following cryptic clues to unravel the mystery of what really happened to their parents-and find out if they're still alive.